Interdisciplinary Research and Impact (Global Challenges 4/2019). Issue 4 (5th April 2019) - Brown, Rebekah; Werbeloff, Lara; Raven, Rob
Abstract : This special issue brings together international, interdisciplinary sustainable development research collaborations that seek to influence policy and practice in their respective domains. The contributions to this issue cover a variety of empirical fields, geographical scopes, and disciplines. Further details can be found in article number1900020 .